Pengaruh Kompres Air Hangat terhadap Intensitas Nyeri Disminore pada Remaja - Nova S.J Sianturi; Nurmalasari Nurmalasari; Nurviza Arianti Azma (Jurnal Bidan Mandiri, 2024)
Introduction Continuous contraction of abdominal muscles that occurs continuously due to the release of blood during menstruation causes dysmenorrhea. Menstrual pain or dysmenorrhea, besides being the most common issue, also becomes a reason for the decrease in women's activities during menstruation, such as missing school. Handling this issue through non-pharmacological means needs to be developed, for example, by using warm water compress. The purpose of this research is to determine the effect of warm water compress on the reduction of menstrual pain intensity in adolescents in the Sekip Village, Lubuk Pakam District, Deli Serdang Regency in 2022. The research method used is pre-experimental with a one-group pre & post-test design. The sample was obtained based on inclusion criteria, amounting to 30 individuals using purposive sampling technique. Paired sample t-test was used to analyze the relationship testing. The Numeric Rating Scale (NRS), which is an observation sheet for pain, is the research instrument used in data analysis, employing the Shapiro-Wilk test. The research results indicate that the average dysmenorrhea score before using warm compress is 6.93, with a standard deviation of 1.23 and a median score of 7.00. Before using warm compress, the average discomfort score for dysmenorrhea is 4, with a maximum of 9. After using warm compress, the average level of dysmenorrhea pain is 3.90 with a standard deviation of 1.24 and a median score of 4.00. After using warm compress, the average discomfort score for dysmenorrhea ranges from 1 to a maximum of 6. In conclusion, warm compress has an impact on the degree of discomfort from dysmenorrhea in adolescents in Sekip Village, Lubuk Pakam District, Deli Serdang Regency (ρ=0.000). Warm compress is expected to be used as one of the treatments to help adolescents suffering from dysmenorrhea reduce discomfort during menstruation.